Assessment of Factors Associated with Dropout for Pentavalent Vaccine in Tertiary Care Hospital of Kathmandu, Nepal (Nepal Medical College Journal, 2020)
Immunization is one of the most cost-effective public health measures as it has helped in huge reduction of disease, disability and death from different infectious diseases in children by protecting them from vaccine preventable diseases. The current study aimed to study factors associated with dropout for pentavalent vaccine in tertiary care hospital of Kathmandu. A longitudinal observational study using purposive sampling technique was conducted among 196 infants. The information was obtained using self-constructed structured questionnaire from parents visiting Community Medicine OPD of Nepal Medical College Teaching Hospital. The information regarding socioeconomic characteristics of mother, gender of the infant, place of delivery of child, birth order and reasons for dropout of pentavalent third dose were taken. The dropout of third dose pentavalent vaccine was mainly seen in infant of parents living in rented house and according to gender wise, dropout was high among male infants. The different reasons for dropout of vaccine were busy parents, forgotten date, visit to other immunization centres and sick infants. Among these, the main reason for dropout of vaccine was due to infants getting sick during the time of immunization. The dropout rates between first and third dose of pentavalent vaccine were 26.3% and 30.4% respectively for two consecutive months and the overall dropout rate was 28.35%. Also, literacy level of the mother was directly associated with the immunization visit of the infant as, maximum number of infants of illiterate mother were absent for third dose of pentavalent vaccine as opposed to no absentee among master degree holding mothers. Thus, the present study provides valuable information regarding the factors associated with dropout for pentavalent vaccine.